The main characteristics and specific qualities of the economic relations between the Republic of Serbia and the Russian Federation - Božović Ivan (Ekonomski Pogledi, 2014)
Serbia has the established diplomatic relations with many countries from all over the world; however, the political and economic cooperation in particular are not on the same level for all of them. The overall relations between Serbia and the Russian Federation fall under the first-class, strategic and friendly relations, and as such are on the very top of the foreign policy priorities for the Serbian Government. The economic relations between Serbia and Russia went through different phases in the course of history. However, if we look at the period of the so called recent history, i.e. the time since both countries started the process of ownership and general social transformation, it can be concluded that the economic relations are very successful, but not wholly consistent with the excellent political relations, and that there are numerous unused possibilities. At the beginning of the 21st century, the Russian Federation and Serbia signed the Free Trade Agreement, thus paving the way into the new age of even stronger and more comprehensive economic relations, which put our economy in a more privileged position compared to the rest of the countries (except for the countries in Customs Union with Russia). The agreement applies to around 95% of produce, exempt from customs duties while being imported from Serbia. Bearing in mind the importance of the economic cooperation with Russia, the author's intention is to point to enormous benefits not completely taken advantage of, as well as the greatest issues which burden the economic relations between the two countries. Through application analysis, the authors arrived to certain conclusions later in the study, hence the final section includes the suggested set of activities and measures, aimed to overcoming the shortcomings which burden the economic relations and prevent the possible extent of trade between Serbia and Russia.